PROFIL MEDIA PEMBELAJARAN FLASH MATERI PERTUMBUHAN DAN PERKEMBANGAN PADA TUMBUHAN - DIANITA PUSPITASARI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Flash media is a media that can visualize something which is abstract into concrete and tangible. Development of research aims to produce flash learning media in the topic of growth and development in plants which is feasible theoritically. The feasibility of media based on the feasibility of material and media. This development research used ASSURE model which consist of six phases, starts from analyze learner until evaluate and revise. Then, the media tested limitedly toward students. The result of media feasibility theoritically consist of topic and media. The topic and material very fasible and feasibility got the same value about 3,64 and 3,62. Based on the result of theoritically feasible, flash media of growth and development in plants is feasible to be used in the learning process. Keywords : Growth and Development in Plants Flash Media, Theoretical feasibility